Forests in Peru: importance, management and perspectives in a climate change context - Paz Majluf, Betsaida Yamile (2018)
This written work intends to submit a brief but comprehensive panorama of the Peruvian Amazonian forests situation. Hoping to achieve it, the first item entitled: “The Amazon for the World, the Region and Peru”, makes an approach of the diverse functions that this basin fulfills in these three levels; the second item: “The Amazonian Forests National Management”, seeks to bring us closer to the state of forest management, including a sub-item “Deforestation”, which pursues to encompass this complex problem; the third item: “Perspectives and Recommendations for Forests Management in a Climate Change context”, basically deals with various aspects to be considered, in a national context, for a future conservation of the Amazonian forests; and finally, there are a couple of global conclusions.